2014
DOI: 10.11604/pamj.2014.18.334.4206
|View full text |Cite
|
Sign up to set email alerts
|

Latrine utilization and associated factors among people living in rural areas of Denbia district, Northwest Ethiopia, 2013, a cross-sectional study

Abstract: IntroductionIn Ethiopia up to 60% of the current disease burden is attributable to poor sanitation. Latrine facility coverage is increasing since Health Extension Program started, whereas less attention to quality and utilization of latrine facilities in rural Ethiopia.MethodsA community based cross-sectional study design with multistage sampling technique was employed to collect data from total of 806 households.ResultsA total of 801 households with latrines were assessed for their latrine utilization status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
73
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 4 publications
16
73
6
1
Order By: Relevance
“…This might be because school age children are "agent of change" in pacing the behavior and practice of their family and community at large. This finding is similar with a study done Denbia district, Northwest Ethiopia [23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This might be because school age children are "agent of change" in pacing the behavior and practice of their family and community at large. This finding is similar with a study done Denbia district, Northwest Ethiopia [23].…”
Section: Discussionsupporting
confidence: 93%
“…This could be going to open field is perceived by the community to provide natural manure which would in turn improve the fertility of their fields as in case of cow dung and people were found unwilling to take responsibility of maintaining the cleanliness of these latrines. Similarly, study done in Denbia district, Northwest Ethiopia identified long live habit (60.4%) and considering open defecation comfortable (18.9%) as the most common reason for not utilizing of latrine by the households [23]. Study done in Hultu Ejju Enessie also identified non functionality of latrine and staying out for work as a reason for not using latrines [18].…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, a study done at Denbia district, Northwest Ethiopia, 86.8% of the respondents were using latrines (Yimam et al, 2014), this is almost the same with non-CLTSH communities of this study. However, the UCLTSH implementers are still better in latrine utilization compared to Denbia district.…”
Section: Discussionsupporting
confidence: 80%
“…Sehingga, perlu upaya untuk dapat menyentuh nurani masyarakat. Hal ini erat kaintannya dengan peran tokoh masyarakat yang telah diberikan pelatihan STBM untuk mendampingi mereka dalam upaya menuju stop BABS (Yimam, et al, 2014). Jika kesadaran masyarakat Kelurahan Tirto tinggi, maka bisa mendongkrak komitmen untuk mencapai kelurahan ODF.…”
Section: Pendahuluanunclassified